Sport-specific policies and factors that influence international success: The case of tennis - Brouwers, J.; Sotiriadou, P.; de Bosscher, V. (Sport Management Review, 2015)
Countries continue to seek ways to achieve and sustain elite athlete success. However, competitive advantages in elite sport are largely found within individual sports` contexts and policies. This paper uses tennis as an exemplar and mixed methods to examine sport-specific policy and other factors that influence international success. Thirty-five international tennis experts participated in a questionnaire which combined (a) open questions, and (b) Likert scale questions, based on the Sport Policy Factors that Lead to International Success (SPLISS) model. The findings support the significance of the SPLISS model at a tennis specific level. The most significant contribution of this paper rests on the emergence of two contextual themes, namely culture and commercial environment, which help explain the context within which tennis operates. These findings are important for understanding the ways elite sport success is fostered in professional sports like tennis and potentially transferring that knowledge to other commercialised sports. The paper advances the theoretical understanding of the combined meso-level and contextual factors at a sport-specific level that influence international success. The practical implications address high performance directors` and sport policy makers` challenge of nurturing and enhancing the tennis culture and commercial environment.